The Optimization of Solar Heating System with Seasonal Storage Based on a Real Project. (2015) - Li, Xiangli; Liu, Meishan; Duanmu, Lin; Ji, Yongming
Abstract: This article mainly describes a real project heating by solar energy. By introducing its details and the control strategies, we may discover the advantages in utilizing the technology and the disadvantages to improve. By establishing a TRNSYS model of the project and design a orthogonal schedule L36 (6 3 *3 3 ), we can simulate the operating condition to discover the relationships between each influences thus provide a optimum proposal. We can come to a conclusion that if the parameter of H/D of the pool is about 0.6-1.5, the system will get better heat storage. Of all influences, the solar areas takes up the vital part, the volume of the pool takes the second place. To this project, it is suggested the parameter to be 260m 2 collectors, 500m 3 pool, 30m 3 tank, the storing pump runs when the tank outlet temperature reaches 55̊C and the storing begins from May 1 st .